Sorting through affirmative action: Three field experiments in Colombia - Marcela Iba\~nez; Ashok Rai; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
Affirmative action to promote women's employment is a intensely debated policy. Do affirmative action policies attract women and does it come at a cost of deterring high qualified men? In three field experiments in Colombia we compare characteristics of job-seekers who are told of the affirmative action selection criterion before they apply with those who are only told after applying. We find that the gains in attracting female applicants far outweigh the losses in male applicants. Affirmative action is more effective in areas with larger female discrimination and deters male job-seekers from areas with low discrimination.
Keywords: J21; J24; J48; C93; 330; Field experiment; Affirmative action; Labor market; Gender participation gap